The league. The complete season 4 [videorecording (DVD)] - Schaffer, Jeff (Director); Schaffer, Jeff (Director); Marcus Schaffer, Jackie; Marcus Schaffer, Jackie; Aselton, Katie, 1978-; Duplass, Mark; Kroll, Nick; Kroll, Nick (Twentieth Century Fox Home Entertainment, 2018)
Follows six friends as they participate in a fantasy football league, and the lengths they'll go to win.